"As soon as you've had the baby that's it…" a qualitative study of 24 postnatal women on their experience of maternal obesity care pathways. (December 2016) - Dinsdale, Sarah; Branch, Kay; Cook, Lindsay; Shucksmith, Janet
Abstract Background Maternal obesity is associated with risks to mother and infant, and has implications for healthcare costs. United Kingdom (UK) levels of maternal obesity are rising, with higher prevalence in North East (NE) England, where this study was set. Pregnancy is often seen as an opportune time for intervention – a 'teachable moment' - which is ripe for promoting behaviour change. In response to rising obesity levels, a National Health Service (NHS) Foundation Trust in NE England implemented three maternal obesity care pathways contingent on Body Mass Index (BMI) at time of booking: pathway 1 for those with BMI ≥30 kg/m2 ; pathway 2 for BMI ≥35 kg/m2 ; and pathway 3 for BMI ≥40 kg/m2 . These incorporated relevant antenatal, intrapartum and postnatal clinical requirements, and included a focus on weight management intervention. This evaluation explored the accounts of postnatal women who had been through one of these pathways in pregnancy. Methods The study used a generic qualitative approach. Semi-structured interviews were carried out to explore the views and experiences of 24 recent mothers (aged 20–42), living in NE England, who had commenced on one of the pathways during pregnancy. Interviews explored experiences of weight management support during and after pregnancy, and perceived gaps in this support. Data were analysed using thematic content analysis. Results Three main themes emerged reflecting women's views and experiences of the pathways: communication about the pathways; treating obese pregnant women with sensitivity and respect; and appropriate and accessible lifestyle services and information for women during and after pregnancy. An overarching theme: differences in care, support and advice, was evident when comparing the experiences of women on pathways 1 or 2 with those on pathway 3. Conclusions This study indicated that women were not averse to risk management and weight management intervention during and after pregnancy. However, in order to improve reach and effectiveness, such interventions need to be well communicated and offer constructive, individualised advice and support. The postnatal phase may also offer an opportune moment for intervention, suggesting that the simple notion of seeing pregnancy alone as a window of opportunity or a 'teachable moment' should be reconsidered.